Sustainable Rice Production in India Through Efficient Water Saving Techniques - Vijayakumar, S.; Karunakaran, V.; Gobinath, R.; Basavaraj, K.; Goud, B. Raghavendra; Sha, Naseeruddin; Manasa, Vakada; Aravindan, S. (Chronicle of Bioresource Management, 2023)
Decreasing irrigation water availability, declining ground-water table, emission of greenhouse gas, indiscriminate use of pesticides (insecticides & fertilizers), intensive rice-rice cropping system, declining soil fertility and other environmental problems due to practice of unsustainable rice production practices are of serious concern. Action to address these multiple issues associated with rice cultivation should be taken immediately to ensure sustainable agricultural development in the post-Industrial era. In this article, we discussed in detail the paradox of the Indian rice scenario, perceptions that are not true in rice cultivation, the various problem associated with rice production and finally proven technologies to address the multiple issues associated with rice production.